Mistake-proofing : achieving zero defects - Shingo, Shigeo, 1909-; Bollinger, Steven R.; Society of Manufacturing Engineers (Manufacturing insights)
Describes mistake-proofing ("poka yoke") and how this technique, developed by Shigeo Shingo, is used to achieve zero defects.